Dynamics and gain in highly-excited InGaN MQWs - Taylor, R; Kyhm, K; Smith, J; Rice, J; Ryan, J; Someya, T; Arakawa, Y (2002)
The Kerr gate technique is used to time-resolve the gain in an In0.02Ga0.98N/In0.16Ga0.84N multiple quantum well sample. A new way of analyzing the data in such a variable stripe length method gain experiment is used to analyze both the time-integrated and time-resolved spectra. We confirm that the stripe length dependence of the gain in the multiple quantum wells under nanosecond excitation is caused by the change of the chemical potential along the excited stripe due to the interaction of the carrier and photon densities, and the gain threshold density is estimated. A trial function assuming a Lorentzian line shape for the stripe length dependence of the gain is compared with the edge emission intensity. This is found to fit very well with our data, even beyond the saturation region. Furthermore, we have extended the investigation to examine the dynamics of the emission and gain. These measurements suggest that the photoexcited carriers must localize (possibly at indium-rich sites) before strong stimulated emission is seen. © 2002 Elsevier Science B.V. All rights reserved.